The Groping Youth '90. (Seoul : National Museum of Contemporary Art, 1990)
Kang, Kyung Koo ; Kwak, Jung Myung ; Kim, Mi Soon ; Kim, Sun Doo ; Kim, Sun Hyoung ; Kim, Seong Eun ; Kim, Sung Ho ; Kim, Seong Heul ; Kim, Eun Sook ; Kim, Ho Suck ; Kim, Hoon ; Moon, Bong Sun ; Park, Sung Tae ; Park, In Hyun ; Bae, Sung Hwan ; Sa, Suk Won ; etc.
The Groping Youth '90, The National Museum of Contemporary Art, Seoul, 20.06. - 19.07.1990
boek